Evidence inconclusive - comment on article by Schoenfeld et al. Issue 1 (December 2016) - Beale, David
Abstract This article comments on the study by Schoenfeld, et al. entitled "The effect of protein timing on muscle strength and hypertrophy: a meta-analysis" and discusses how the methodology led to inconclusive results.